GAMBARAN KADAR ENZIM KOLINESTERASE DALAM DARAH PADA KELOMPOK TANI MEKAR NADI DI DESA BATUNYA KECAMATAN BATURITI - nyoman mastra (Meditory : The Journal of Medical Laboratory, 2018)
Background: Pesticides is poison and dangerous materials. It can cause negative effects to human health directly or indirectly. Blood cholinesterase enzyme analysis is one of the methods to indicate that someone is poisons by pesticide. Purpose: This research is a descriptive study. The aim of this study is to illustrate the cholinesterase levels in the farmer’s blood especially the farmers in Batunya village. Methods: The population in this research was 30 farmers who are the members of Groups Tani Mekar Nadi. The sampling method that used in this research was saturation sampling. Data collection used the questionnaire. The test-mateChE cholinesterase test system (model 400) is the device that used to check the level of cholinesterase in the farmers’ blood. Result: The result show that 22 peoples (73,3%) cholinesterase level was abnormal. In the other hand, 8 of the farmer (26,7%) has normal level of cholinesterase. Conclusion: From the result it can be concluded that it’s still important to monitor the level of cholinesterase in farmers’ blood to increase awareness towards the danger of pesticide, always use self-protection device, and conducting a good pesticide management.Keywords: pesticide, cholinesterase, poisoned